1998
DOI: 10.1093/jac/42.2.211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a component of tea (Camellia sinensis) on methicillin resistance, PBP2' synthesis, and beta-lactamase production in Staphylococcus aureus

Abstract: Extracts of tea (Camellia sinensis) can reverse methicillin resistance in methicillin-resistant Staphylococcus aureus (MRSA) and also, to some extent, penicillin resistance in beta-lactamase-producing S. aureus. These phenomena are explained by prevention of PBP2' synthesis and inhibition of secretion of beta-lactamase, respectively. Synergy between beta-lactams and tea extracts were demonstrated by disc diffusion, chequerboard titration and growth curves. Partition chromatography of an extract of green tea on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 16 publications
7
92
0
Order By: Relevance
“…Green tea was also reported to have a synergistic effect with β-lactam antibiotics against MRSA [24][25][26][27][28] , It was also reported that the main component of tea polyphenols, epigallocatechin gallate can reverse methicillin resistance of MRSA by inhibiting the synthesis of PBP2 [29] , Epigallocatechin gallate not only increases the activity of β-lactams but also increases the activity of non-β-lactam cell wall biosynthesis inhibitors [26] .…”
Section: Discussionmentioning
confidence: 98%
“…Green tea was also reported to have a synergistic effect with β-lactam antibiotics against MRSA [24][25][26][27][28] , It was also reported that the main component of tea polyphenols, epigallocatechin gallate can reverse methicillin resistance of MRSA by inhibiting the synthesis of PBP2 [29] , Epigallocatechin gallate not only increases the activity of β-lactams but also increases the activity of non-β-lactam cell wall biosynthesis inhibitors [26] .…”
Section: Discussionmentioning
confidence: 98%
“…In order to assess the effect of combinations of ethanolic extract and antibiotic, the MIC values for antibiotic were determined to be as a reference point for defining the interactions [26] . Synergistic effects resulting from the combination of antibiotics with various plant extracts have been studied earlier against MRSA or MSSA [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . From this study, ethanolic extract of E. elaterium fruits is very efficient in treating infectious diseases caused by MRSA and may also helpful for treating diseases caused by C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several antibiotic adjuvants have been evaluated for their action as resistance-modifying agents (RMAs) (Hemaiswarya et al, 2008), i.e., compounds that can modify or inhibit the bacterial mechanisms of resistance, so that antibiotics can efficiently kill the resistant bacteria. Several RMAs were already described (Chan et al, 2011;Gibbons et al, 2003;Khan et al, 2006;Roccaro et al, 2004;Schmitz et al, 1998;Yam et al, 1998). Efflux pump inhibitors (EPIs) are important examples of RMAs since they can prevent the extrusion of an antibiotic to the exterior of the cell and thus allow the antibiotic to act efficiently against bacteria.…”
Section: Introductionmentioning
confidence: 99%